Perancangan dan Implementasi Aplikasi Internet Radio Menggunakan Multimedia Database Melalui Penerapan Ontology dan Metadata - Erwansyah, M. Rudy; Setiawan, Ong Budi; Abbas, Bahtiar S. (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The study aims to analyze, design and implement the internet radio application used in managing the audio data on Heartline FM radio station. In this application, the audio data which has been managed can be used in a radio broadcast scheduling. The scheduled radio broadcast is then forwarded to the webcast server to be transmitted through the Internet. This research carries out analysis, design and implementation using Object Oriented Analysis and Design method and Lean Architecture for Agile Software Development. The program component design consists of: (1) software functional system, (2) user interface, (3) problem domain model, which in internet radio application is divided into five subcomponents, namely: audio-indexing-retrieval, scheduling, reporting, user and ontology. In the implementation of internet application of this radio, the audio data management uses multimedia database by applying metadata and ontology, so that the process of indexing and retrieval can be reused quickly on the broadcast. This application can also be used in carrying out the radio broadcast automatically during specified hours. This internet radio application has been able to meet the needs of radio Heartline.